A behavioral portfolio analysis of retirement portfolios - Nico Singer (Universität Rostock, Institut für Volkswirtschaftslehre, 2011)
To most individuals saving for retirement is the number one financial goal. However, it reveals a complex task and induces serious behavioral problems which cannot be explained by traditional economic theory. This paper investigates the role of behavioral asset selection on retirement portfolios in Germany. Simulated behavioral portfolios show (i) an impact of emotions since pessimism (optimism) induces the most conservative (aggressive) portfolio, (ii) concentrated portfolios with a large position in only one secure asset and a small position in a risky portfolio, and (iii) a large difference to mean-variance portfolios in terms of level of diversification. I conclude that behavioral portfolio theory has remarkably power in understanding, describing and selecting retirement portfolios in Germany. The results have several implication for financial planning, e.g. for an auto-pilot solution to encourage people to more retirement saving.
Keywords: G11; 330; behavioral portfolio choice; decision making under risk; retirement portfolios; Private Altersvorsorge; Anlageverhalten; Portfolio-Management; Entscheidung bei Risiko; Schätzung; Deutschland